Removal of heavy metals from wastewater using biochars: adsorption and mechanisms. Issue 1 (31st December 2022) - Ye, Qingqing; Li, Qianhui; Li, Xin
ABSTRACT: The physicochemical properties and heavy metals adsorption capacities of biochars derived from cattle manure (CM) and cherry wood (CW) were systematically investigated and compared. The results showed that the yields, pH and the ash content of cattle manure biochars (CMB) were higher due to high levels of mineral constituents in CM. CMB6 and CWB6 showed higher aromaticity and polarity, whereas CMB4 and CWB4 carried higher oxygen-containing functional groups. CMB6 exhibited the maximum adsorption capacities for Pb 2+ (40.8 mg·g −1 ), Cd 2+ (24.2 mg·g −1 ), and Ni 2+ (25.1 mg·g −1 ), with relatively higher adsorption capacities for Pb 2+ . The adsorption isotherms fitted Langmuir model, indicating that the heavy metal adsorptionoccurred via a combination of physical and chemical adsorption mechanisms. The quantitative analysis showed that the interaction with minerals was the dominant mechanism, especially accounting for about 70% in CMB6. This study provides important information for comprehensive recycling utilization of biomass for sustainable development. Graphical Abstract: uf0001